Sex-specific Transcriptomic Differences From Human Dorsal Root Ganglia Associated With Painful Radiculopathy. (1st September 2019) - North, Robert Y; Li, Yan; Ray, Pradipta; Rhines, Laurence D; Tatsui, Claudio E; Rao, Ganesh; Kim, Yeun Hee; Zhang, Bo; Dussor, Greg; Kim, Tae Hoon; Price, Theodore; Dougherty, Patrick M
Abstract: INTRODUCTION: Women are at greater risk to suffer from many chronic pain conditions, more often report painful symptoms in epidemiological studies, and demonstrate greater pain sensitivity to experimentally measured pain responses. There is growing evidence from animal models for sex-specific biological differences in nociception, particularly involving primary afferent neurons, that may contribute to these differences. However, the details and extent of sex-specific differences associated with pain in human afferent neurons has not been previously investigated. METHODS: Human dorsal root ganglia (DRG) and medical histories were obtained from patients undergoing spinal surgery that necessitated sacrifice of spinal nerve roots as part of standard of care. Clinical data for presence of painful radiculopathy was obtained through retrospective review of medical records or collected at study enrollment. RNA sequencing (RNA-seq) was performed on 21 DRG from 15 patients with variable presence of radicular pain reported in a corresponding dermatome. Differential expression analysis for male w/pain (MP) vs female w/pain (FP) samples was performed with thresholds for robustly expressed autosomal genes (TPM >3.0), fold change of 2.0 or higher, with false discovery rate (FDR) <0.05. RESULTS: Comparison of the MP and FP cohorts yielded 575 differentially expressed genes with 426 upregulated in MP and 149 upregulated in FP. Gene set enrichment analysis demonstrated significant differences in genes related to inflammation and immune regulation (increased MAPK and BDNF signaling in MP, increased Rhodopsin-like GPCR in FP) and differing clusters of spinal cord injury-associated genes (TLR4, AIF1, OMG, C1QB increased in FP, EGR1, NR4A1, ZFP36, BTG2, MYC in MP). CONCLUSION: Utilizing RNA-seq of human DRG innervating regions of pain, this study provides the first demonstration of sex-specific differences for the biology of pain within the dorsal root ganglion in humans and implicates the immune system as a critical influence in these differences.